The potential of molecular self-assembled monolayers in organic electronic devices - Halik, Marcus; Hirsch, Andreas (Advanced Materials, 2011)
Functionalized molecules that organize to self-assembled monolayers (SAMs) are gaining importance in organic electronic devices. They are fully compatible with flexible substrates, are amenable to low-cost processing, and show reliable film-forming behavior. Highly integrated devices, such as sensor arrays or memories, have also been demonstrated. Starting from auxiliary layers, which improve and modify surfaces and interfaces in traditional thin-film devices, the applications of SAMs develop towards molecular scale electronics, including active molecular device layers and multifunctional SAMs, which fulfill several layer functions of a device within one monolayer. Mixed SAMs make new and tunable device features possible, by stoichiometric control of the composition of different SAM-forming molecules. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.